DAMPAK PENERAPAN GOOD GOVERNANCE DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH KABUPATEN KUPANG - Selfesina Samadara; Jennie S. Sir; Zainudin A. Zainudin; Moni Y. Siahaan (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: The quality of Local Government Financial Statements is an important indicator of public accountability and financial transparency. In Kupang Regency, the improvement of financial reporting quality requires strong governance practices and competent human resources in financial management. This study aims to examine the effect of good governance and human resource competency on the quality of Local Government Financial Statements. Method: This research employed a quantitative approach with a causal associative design. The population consisted of financial and asset management officers from 52 regional apparatus organizations in Kupang Regency. A saturated sampling technique was applied because the population was relatively accessible, resulting in 208 respondents. Data were collected using structured questionnaires and analyzed through multiple linear regression.Results: The reliability test showed that all research instruments were reliable, with Cronbach’s Alpha values of 0.913 for good governance, 0.907 for human resource competency, and 0.918 for financial statement quality. The regression analysis produced the equation Y = 0.673 + 0.485X₁ + 0.326X₂ + e. The results indicate that good governance has a positive and significant effect on the quality of Local Government Financial Statements, with a significance value of 0.000. Human resource competency also has a positive and significant effect, with a significance value of 0.000. The coefficient of determination shows that 61.2% of the variation in financial statement quality is explained by good governance and human resource competency.This study concludes that good governance and human resource competency significantly contribute to improving the quality of Local Government Financial Statements in Kupang Regency. Strengthening transparent, accountable, and regulation-compliant governance, supported by competent financial officers, is essential to produce reliable and high-quality financial reports.Kupang Regency. Keywords: Financial Statement Quality, Good Governance; Human Resource Competency; ; Kupang Regency, Local Government;